The relationship between resource elemental deficiencies and zooplankton community structure and dynamics - McCarthy, Valerie (Trinity College (Dublin, Ireland). Department of Zoology, 2007)
Ecological stoichiometry is the study of the balance of elements in ecological interactions and processes. Recent theoretical and experimental work suggests that consideration of stoichiometric constraints on zooplankton production may substantially improve our understanding of zooplankton community composition and species interactions. This study aimed to examine the role of stoichiometry in influencing zooplankton community structure, species occurrence and seasonal patterns of succession in six lakes in the west of Ireland. Stoichiometric processes were viewed in the context of the overall biotic and abiotic environment which may also potentially influence zooplankton community structure and dynamics.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin